2005
DOI: 10.1177/15353702-0323006-05
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Alcohol Exposure and Fetal Programming: Effects on Neuroendocrine and Immune Function

Abstract: Alcohol abuse is known to result in clinical abnormalities of endocrine function and neuroendocrine regulation. However, most studies have been conducted on males. Only recently have studies begun to investigate the influence of alcohol on endocrine function in females and, more specifically, endocrine function during pregnancy. Alcohol-induced endocrine imbalances may contribute to the etiology of fetal alcohol syndrome. Alcohol crosses the placenta and can directly affect developing fetal cells and tissues. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
130
1
4

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(144 citation statements)
references
References 102 publications
9
130
1
4
Order By: Relevance
“…Zhang at al. have demonstrated that alcohol consumption during pregnancy increases Hypothalamic-PituitaryAdrenal (HPA) responsiveness in rat pups in such a way that ethanol-exposed neonates exhibit reduced increase responsiveness in early and pre-weaning life (Zhang et al, 2005). The exact nature and significance of this disturbed hormonal homeostasis still needs to be determined but it is possible that insufficient neonatal corticosteroid levels might be an underlying indicator for inadequate lung surfactant production.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang at al. have demonstrated that alcohol consumption during pregnancy increases Hypothalamic-PituitaryAdrenal (HPA) responsiveness in rat pups in such a way that ethanol-exposed neonates exhibit reduced increase responsiveness in early and pre-weaning life (Zhang et al, 2005). The exact nature and significance of this disturbed hormonal homeostasis still needs to be determined but it is possible that insufficient neonatal corticosteroid levels might be an underlying indicator for inadequate lung surfactant production.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, preliminary data indicate that the tibia of fetal guinea pigs prenatally exposed to ethanol also has increased fat content (Keiver and Brien, unpublished data), thereby suggesting that ethanol also alters the balance between adipogenesis and osteogenesis in the fetus. In addition, ethanol intake is known to affect of number of maternal/fetal systems, including the glucocorticoid [40], insulin-like growth factor [3] and calcium-regulating [1,15,16, and 17] systems, all of which could potentially affect bone development.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies exist in the human literature on the effects of alcohol consumption on maternal ACTH and cortisol concentrations or on the HPA function of alcohol-exposed children (Zhang et al, 2005). Early human FAS studies on HPA function are based on limited sample size and unreliable self-reporting (Root et al, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of alcohol consumption among women of child-bearing age remains essentially unchanged despite considerable efforts to educate women about the harmful consequences of alcohol consumption during pregnancy (Caetano et al, 2006;CDC, 2004;Institute of Medicine, 1996;Maternal and Child Health (MCH) Data Report, 2003;NIAAA, 2000) requiring the need to consider other approaches to reduce the negative impact of prenatal alcohol exposure (Cudd, 2005). Numerous hypotheses have been proposed to account for the teratogenic effects of alcohol of which alcohol induced alterations in hypothalamic-pituitaryadrenal (HPA) axis, and hypothalamus-pituitary-thyroid (HPT) axis function are popular (For review, see Zhang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%